2021
DOI: 10.28991/cej-2021-03091674
|View full text |Cite
|
Sign up to set email alerts
|

Field Study of the Noise Exposure Inside Running Metro Unit

Abstract: The noise levels inside metro units are considered a significant problem that makes passengers suffer from severe damage, especially for those who use the metro periodically. This research evaluates the acoustic environment inside the metro car and studies factors affecting the noise levels inside metro units and developing models for estimate noise in the metro unit while moving between stations. Greater Cairo Metro (GCM) Line 1 has been selected as a case study. A sound level meter was used to measure the eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Industrial and traffic noise severely affects both auditory and non-auditory physiology in human including hearing loss [9], irregular pattern of heartbeat, psychology related problem and high blood pressure [10], stress and irritation, difficulty in sleeping, reduced work efficiency as well as difficulty in understanding the topic of conversation [11] In a study conducted in Indonesia the noise recorded inside the Argo Parahyangan train was 67.5 -74.2 dBA for executive class in daytime and for night-time it was 69.1 -75.2 [12]. In a study conducted by [13] it was found that the noise inside an underground metro station is 5 dB higher than the open metro stations, because of reflective s It is surfaces and reverberations. Train noises are in the frequency of 400-4000 Hz [14].…”
Section: Who Pyramid Of Health Effect Of Noisementioning
confidence: 99%
“…Industrial and traffic noise severely affects both auditory and non-auditory physiology in human including hearing loss [9], irregular pattern of heartbeat, psychology related problem and high blood pressure [10], stress and irritation, difficulty in sleeping, reduced work efficiency as well as difficulty in understanding the topic of conversation [11] In a study conducted in Indonesia the noise recorded inside the Argo Parahyangan train was 67.5 -74.2 dBA for executive class in daytime and for night-time it was 69.1 -75.2 [12]. In a study conducted by [13] it was found that the noise inside an underground metro station is 5 dB higher than the open metro stations, because of reflective s It is surfaces and reverberations. Train noises are in the frequency of 400-4000 Hz [14].…”
Section: Who Pyramid Of Health Effect Of Noisementioning
confidence: 99%
“…Mass Rapid Transit (MRT) has been considered as a prominent type of public transit systems in many countries [1]. Especially in developed regions, MRT has become a major urban transportation system because of its advantages of mass service, convenience, punctuality, and fast speed [2]. In addition, it is an eco-approach with capacity to reduce the air pollutants caused by traffic congestion from private vehicle usage [3][4][5].…”
Section: Introductionmentioning
confidence: 99%